2020
DOI: 10.3390/coatings10080796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bias Voltages on the Structural, Mechanical and Oxidation Resistance Properties of Cr–Si–N Nanocomposite Coatings

Abstract: Cr–Si–N nanocomposite coatings were deposited by multi-arc ion plating under different bias voltages. The influences of bias voltage on composition, microstructure, surface morphology and mechanical properties of Cr–Si–N nanocomposite coatings were investigated in detail. The HR-TEM, XRD, and XPS results confirmed the formation of nanocomposite structure of nanocrystalline of CrN embedded into the amorphous phase of Si3N4. The particle radius of CrN can be calculated from the half-width of the diffraction peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[32][33][34][35] In the literature materials such as Ni-P/nano-SiC, Carbon nanotubes reinforced electrospun chitosan nanocomposite, CrSiN/CrN/Cr and Mg-Al-Layered Double Hydroxide were used to protect the surface of AZ31. [36][37][38][39] One such popular metal Al whose film was coated on AZ31 in our other work and found it to be a suitable protective coating. 40 Each of the material system has its own merits and demerits.…”
Section: Introductionmentioning
confidence: 80%
“…[32][33][34][35] In the literature materials such as Ni-P/nano-SiC, Carbon nanotubes reinforced electrospun chitosan nanocomposite, CrSiN/CrN/Cr and Mg-Al-Layered Double Hydroxide were used to protect the surface of AZ31. [36][37][38][39] One such popular metal Al whose film was coated on AZ31 in our other work and found it to be a suitable protective coating. 40 Each of the material system has its own merits and demerits.…”
Section: Introductionmentioning
confidence: 80%
“…A wide range of scientific research is devoted to the study of the material properties of nanostructured coatings with universal [13] and high wear-resistant characteristics [3,[14][15][16]. Among various coatings, nitride nanocomposite or nanolayer systems are studied quite widely [5,7,9,11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of scientific research is devoted to the study of the material properties of nanostructured coatings with universal [13] and high wear-resistant characteristics [3,[14][15][16]. Among various coatings, nitride nanocomposite or nanolayer systems are studied quite widely [5,7,9,11,13,14]. Transition metal nitrides are considered as a protective coating due to their excellent properties in terms of hardness, wear resistance and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11] Thin films of CrSi(O, N) prepared by dc magnetron or rf diode sputtering and annealed to obtain small TCRs and high stability are suggested to be particularly suited for high ohmic thin film precision resistors with a sheet resistivity of up to 20 kΩ. [ 12] To this day, multiple studies performed on the CrÀ SiÀ N surface coatings have demonstrated improvements in mechanical and tribological properties, [ 8a, 13] reduction of friction coefficient, enhanced oxidation, [ 14] and corrosion resistance [ 5a] when compared with CrN surface coatings. This excellent performance has led to the application of CrÀ SiÀ N coatings on the surface of various engineering components and parts.…”
Section: Introductionmentioning
confidence: 99%